ABCD is a square.E and F are respectively the mid points of BC and CD.If R is the mid point of EF prove that ar(∆AER)=(∆AFR)
Answers
Answered by
145
Given:- ABCD is a square. E and F are respectively the midpoints BC and CD. R is the midpoints of EF.
To prove:- ar(Triangle AER) =ar(triangle AFR)
Proof:- In triangle ABE and triangle ADF
AB=AD[sides of a square are equal]
angle ABE = angle ADF [each 90°]
E is the midpoint of BC and F is the
midpoints of CD. [1\2 BC=1/2CD]
by SAS rule,
ar(triangle ABE) is congruent to
ar(triangle ADF)
therfore AE=AF (c. P. C. T) -1
now in triangle AER and triangle AFR
AE=AF[from 1]
ER=RF(R is the midpoint of ED)
AR=AR(common side)
by SSS rule
Triangle AER congruent to triangle
AFR.
Hence( triangle AER) = ( Triangle
AFR)
Thank you ☺️☺️☺️
To prove:- ar(Triangle AER) =ar(triangle AFR)
Proof:- In triangle ABE and triangle ADF
AB=AD[sides of a square are equal]
angle ABE = angle ADF [each 90°]
E is the midpoint of BC and F is the
midpoints of CD. [1\2 BC=1/2CD]
by SAS rule,
ar(triangle ABE) is congruent to
ar(triangle ADF)
therfore AE=AF (c. P. C. T) -1
now in triangle AER and triangle AFR
AE=AF[from 1]
ER=RF(R is the midpoint of ED)
AR=AR(common side)
by SSS rule
Triangle AER congruent to triangle
AFR.
Hence( triangle AER) = ( Triangle
AFR)
Thank you ☺️☺️☺️
Answered by
22
Here's the answer
In ABE and ADF
S - AB = AD (SIDE OF A SQUARE )
A- angle ABE =angle ADF (90)
S- BE = DF ( E and F are the mid points of BC&CD)
Hence , ABE congruent ADF by SAS
AE=AF (cpct)
Now in AER & AFR
S - AE= AF (proved above )
S- AR=AR (common)
S- ER= RF (R is the mid points of EF)
HENCE,
AER & AFR are congruent
And ar(AER)=ar(AFR)
proved.
Similar questions
Math,
9 months ago
Math,
9 months ago
Social Sciences,
9 months ago
Environmental Sciences,
1 year ago